JAYANTIâ€ ROHU- A PROMISING FISH VARIETY FOR IMPROVING AQUACULTURE PRODUCTION - MAHAPATRA, KANTA DAS; SAHA, J N; MURMU, K; RASAL, A; NANDANPAWAR, P; PATNAIK, M (Journal of the Inland Fisheries Society of India, 2021)
Selective breeding program was initiated at ICAR-Central Institute of Freshwater Aquaculture (ICAR-CIFA) in collaboration with Institute of Aquaculture Research (AKVAFORSK) in the year 1992 to improve growth of rohu through selectiveÂ  breeding following combined selection method. The base population was established from five riverine sources i.e. Ganga, Yamuna, Brahmaputra, Sutlej, Gomati and local farm stock of ICAR-CIFA. For each year class one control group was produced using 10-15 male and 10-15 female parents with averageÂ  reeding value for harvest body weight and growth comparison was made with the progeny of selected group. The average realized selection response of harvest body weight after eight generations of selection was estimated to be 18.3% per generation. Multilocational field testing as well as on-farm trials in different parts of India showed significant growth improvement of genetically improved rohu for different generation of selectively bred rohu. The improved rohu popularlyÂ  known as â€œJayantiâ€ has been disseminated to 16 states and different hatcheries of India from ICAR-CIFA. The improved rohu also proved to be feed neutral and effective under all culture practices which have enhanced the acceptance level. Impact assessment study further confirmed superiority of Jayanti strain of rohu over the normal rohu. Disease resistance against Aeromonas hydrophila is added as second trait of selection to rohu breeding program. A wide range of variation in survival was observed among different families of rohu. Based on sire-dam model underlying heritability of survival at end of test was 0.15-0.19. After mass challenge, two lines of rohu have been produced i.e. resistant line andÂ  susceptible line. Resistant line rohu showed significantly higher survival over susceptible line. Estimated genetic correlation between growth and survival was observed to be 0.43. The estimation result showed positive correlation between both the traits in rohu breeding program.Key words: Selective breeding, base population, realized selection response, heritability, "Jayanti" rohu